CRISPR-Cas9 Genome Engineering: Trends in Medicine and Health - Zaib, Sumera; Saleem, Mushtaq A.; Khan, Imtiaz (Mini Reviews in Medicinal Chemistry, 2022)
The ability to engineer biological systems and organisms holds enormous potential for applications across basic science, medicine, and biotechnology. Over the past few decades, the development of CRISPR (clustered regularly interspaced short palindromic repeat) has revolutionized the whole genetic engineering process utilizing the principles of Watson-Crick base pairing. CRISPRCas9 technology offers the simplest, fastest, most versatile, reliable, and precise method of genetic manipulation, thus enabling geneticists and medical researchers to edit parts of the genome by removing, adding, or altering sections of the DNA sequence. The current review focuses on the applications of CRISPR-Cas9 in the field of medical research. Compared with other gene-editing technologies, CRISPR/Cas9 demonstrates numerous advantages for the treatment of various medical conditions, including cancer, hepatitis B, cardiovascular diseases, or even high cholesterol. Given its promising performance, CRISPR/Cas9 gene-editing technology will surely help in the therapy of several disorders while addressing the issues pertaining to the minimization of the off-target effects of gene editing and incomplete matches between sgRNA and genomic DNA by Cas9.
Keywords: chromatin